PERANCANGAN PEMASANGAN ALARM DETECTOR DAN SPRINKLER PADA GEDUNG SUDIRMAN DI KEMHAN RI - AGUNG TRIWIBOWO; KAREL L. MANDAGIE; W.TEDJA BHIRAWA (JURNAL TEKNIK INDUSTRI, 2021)
The complexity of the function of a building along with its existing activities demands a higher level of security, so that the complete fire protection system for the safety of users, managers and buildings is also increasingly needed. The ministry office has a fairly complex structure with supporting facilities that must be guaranteed safe and comfortable, so the building must be equipped with reliable fire safety facilities. Sudirman Building Ministry of Defense of the Republic of Indonesia is one of the buildings that must meet the criteria of safety and safety standards. By using Seven Tools and 5 W 1H, the biggest cause of danger is fire. But from the results of initial observation, it was found that the active protection tool as APAR, alarm, sprinkler in Sudirman Kemhan RI building has not meet in the regulatory standards, so it is probable a fire happened because the facility is not functioning optimally. Based on the standards of SNI 03-3985-2000 and SNI 03-3989-2000, the design of detector and sprinkler alarms in the Sudirman building of MoD of RI is designed to deal with fire hazards appropriately. With a building area of 120 m² and height of 10 m, the design of the detector alarm is placed on the wall and the sprinkler uses an orange color at 53° C with an emission density = 2.25 mm / min, the maximum distance between sprinkler spots 4.6 meters. Used pipe size ½ "with capacity (Q) = 80 liters / min. The design of detector alarms, sprinklers and optimum selection of suitable pipes for use are reviewed from a technical point of view through calculations that provide the right and optimal number and place along the path of the fire-fighting installation project. Based on the calculation of the width and position of Sudirman Kemhan RI building, it is determined to place the detector alarm at three wall points, sprinkler of 20 pieces to overcome the fire hazard with the amount of pipe material with 64 meter pipeline, and with the use of two pumps for water supply for 60 minutes = 42,000 liters. Therefore it is proposed the use of SOP on fire hazard in building Sudirman Kemhan RI as guidance in execution of duty during office hours and outside office hours.Keywords: Fire protection system, Alarm Detector, Sprinkler